Variación de la rentabilidad financiera en función del endeudamiento en la Empresa Ferrocentro UNIMAX - Palacios Zúñiga, María Elizabeth (2024)
The research was carried out with the purpose of evaluating the relationship between indebtedness and profitability in Ferrocentro UNIMAX Company during the period 2015-2021. Adopting a non- experimental quantitative approach, a longitudinal panel design was implemented that addressed descriptive and explanatory aspects of this relationship over time. The collection of information was carried out through bibliographic techniques and detailed data processing, focusing especially on the analysis of the company's financial statements. As results, in terms of the company's financial structure, it was identified that: in 2021, 94% of the company was made up of liabilities, while 6% corresponded to equity, in relation to total asset values; cost of sales represented 87% of revenues, expenses reached 11% and profit was 2%. With respect to the correlational tests and the hypothesis proposed, the alternative hypothesis H1 was confirmed: the variation in profitability is not independent of indebtedness. In addition, the regression model presented an adjusted R-squared coefficient of 0.693 for ROA and 0.761 for ROE, indicating that these models explain the variations in profitability as a function of indebtedness. Thus, the effects of indebtedness on profitability turned out to be positive in the case study, since the company's compliance with its obligations translated into profits. Based on these results, a comprehensive approach was developed to propose concrete strategies aimed at improving the company's economic-financial management. These objectives were oriented towards maximizing resources and exploiting opportunities and strengths, covering aspects related to internal processes, learning and knowledge, customers, and the financial perspective.